Recursos didácticos que motiven la participación activa de los estudiantes en el proceso de enseñanza – aprendizaje de Química. Periodo lectivo 2022 – 2023 - Duarte Sánchez, Juan José (2023)
Didactic resources are essential tools and instruments in the teaching and learning process. They allow students to reach in a significant way, improving their academic performance. The proposed objective was to enhance the academic performance of students, through the implementation of didactic resources that motivate their active participation, in the teaching and learning process of the subject of Chemistry, first year of Baccalaureate, of “Daniel Álvarez Burneo” High school, academic period 2022 – 2023. The inductive method with a qualitative approach was used. Therefore, specific particularities of the educational environment were identified, evidencing the low participation of students in the TLP of Chemistry subject and the lack of implementation of relevant didactic resources. Then, through the search of bibliographic information, the intervention proposal was prepared. According to the nature of the information, it is of the Participatory Action Research type. Based on the diagnosis, through the development of the intervention proposal, which includes didactic resources. The active participation of those involved is promoted, to achieve a significant change in relation to the identified problem. According to the level of knowledge, the research is mixed: exploratory, descriptive and explanatory. Since, reality and information are explored, to describe particularities that allow explaining both the observed facts and the actions to be implemented to change the before mentioned reality. The results obtained determined that didactic resources such as images, infographics, audios, sudoku, pictures, the dice, among others, motivated the active participation of students in the TLP of Chemistry, enhancing their academic performance. This was demonstrated by comparing means before and after the intervention. In conclusion, the implementation of didactic resources, in the Chemistry TPP, motivates the active participation of students and enhances their academic performance. Key words: Academic performance, active participation, didactic tools and instruments, teaching work.